An Assessment of the State of the Art Rainwater Collecting Technologies for Promoting Green Built Environments (International Journal of Innovative Research in Engineering & Management, 2021)
Water shortage, inefficient consumption habits, fast  worldwide population growth, a high demand-to-production  ratio, and a slew of other issues underscore the urgent need to  systematically acquire and use alternative, and, most  critically, renewable water supply options. In addition, the use  of well-designed and maintained rainwater harvesting systems  in the built environment while expanding the focus to a  variety of building typologies is advocated as a possible solution to these systemic problems. In developing and green  building environments, there is a gap in the effective  integration of these design elements to achieve consistent  sustainable results in maintenance plans. Governments are  urged to play an important role in the education, opportunity  creation and support of these decentralized water supply and  consumption systems. as meetings, the potential to properly  merge them with green roofs and green building  environmental criteria, and finally manipulated government  regulations to provide information to overcome the above mentioned problem of intensification of rainfall.
Keywords: Green Built Environment; Government Policies; Rainwater Harvesting Systems; Renewable Water Resources; Water Scarcity